Experimental study on the combustion of low‐calorific NG/N2 in a porous burner - Guanqing Wang; Zhongyu Shi; Guohua Xu; Dan Luo; Jiangrong Xu (Energy Science & Engineering, 2022)
Abstract Large amounts of low‐calorific fuel gas without oxygen (LCFGWO), generated by industry every year, are hardly utilized by the conventional combustion technology. Here, an LCFGWO mixture was simulated by diluting natural gas (NG) with nitrogen (N2), and its combustion under different lower heating values (LHV) was experimentally investigated in a SiC ceramic foam burner via an intermittent operation method. The key operating parameters of the burner (i.e., LHV, superficial velocity, and excess air ratio) were analyzed by focusing on its combustion characteristics (temperature profiles, super‐adiabatic effects, and emissions). The results showed that the initial position of the combustion flame was anchored downstream with decreasing LHV. As the LHV decreased to 3.36 MJ/Nm3, super‐adiabatic combustion began to appear, and the super‐adiabatic ratio slightly increased with decreasing LHV. Further, clean combustion of the NG/N2 mixtures in the burner could be achieved over a wide range of LHV with an optimal excess air ratio ranging from 1.3 to 1.5. Subsequently, the length of the porous medium was discussed in terms of the optimal excess air ratio. Its minimum length required to burn the NG/N2 mixtures was found to decrease exponentially with increasing LHV, and an exponential function was fitted to the experimental data. A mathematic correlation for designing the burner length was obtained by considering the effect of flame propagation velocity. These results are helpful toward the design of porous burners for the clean combustion of low‐calorific NG/N2.